2017
DOI: 10.1111/den.12767
|View full text |Cite
|
Sign up to set email alerts
|

DDW 2016 review: Advances in therapeutic upper gastrointestinal endoscopy

Abstract: This is a review of the abstracts presented at Digestive Disease Week 2016, 21–24 May 2016 in San Diego, CA, USA, focusing on novel advances in therapeutic endoscopy of the upper gastrointestinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A small number of studies have described the relationship of adverse events with the Child-Pugh score. These studies consistently demonstrated that the patients with higher Child-Pugh class scores had more complications overall[ 16 - 18 , 20 ]. Inamdar et al[ 13 ] demonstrated a similar risk of adverse events between the non-cirrhosis group and patients with compensated cirrhosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A small number of studies have described the relationship of adverse events with the Child-Pugh score. These studies consistently demonstrated that the patients with higher Child-Pugh class scores had more complications overall[ 16 - 18 , 20 ]. Inamdar et al[ 13 ] demonstrated a similar risk of adverse events between the non-cirrhosis group and patients with compensated cirrhosis.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, one study also observed lower rates of bleeding when the ERCPs in cirrhosis patients were performed in medium- and large-sized hospitals[ 5 ]. Since only a limited number of studies have described hemorrhage or other adverse events in terms of Child-Pugh class or the type of intervention, no separate analysis could be obtained in our meta-analysis[ 16 - 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…ESD is an interventional procedure for the removal of gastrointestinal lesions that uses a high-frequency electric knife and other equipment to dissect or resect lesions and the surrounding mucosal tissue to achieve complete resection. ESD is noted for its minimal invasiveness, but this technique still has some risks of complications, such as perforation and massive bleeding [7,8]. Although most of the perforations and bleeding are endoscopically manageable, secondary infection and gastrointestinal fistula can occur [9].…”
Section: Introductionmentioning
confidence: 99%